Pemanfaatan Minyak Daun Cengkeh untuk Sintesis 3,4-dimetoksibenzil Sianida sebagai Bahan Dasar Sintesis Isoflavon - Alimuddin, Andi Hairil; Matsjeh, Sabirin; Anwar, Chairil; Mustofa, Mustofa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This research was aimed to utilize eugenol isolated from clove leave oil in the synthesis of isoflavones. Eugenol was usedas a raw material by converting into 3,4-dimethoxybenzyl cyanide through several stages of reactions. These stages weremethylation of eugenol, isomerization of methyleugenol, oxydation of methylisoeugenol, reduction of 3,4-dimethoxybenzaldehyde, halogenation of 3,4-imethoxybenzyl alcohol and nitrilization of 3,4-dimethoxybenzyl chloride to3.4-dimethoxybenzyl cyanide. Methylation of eugenol using dimethylsulfate and NaOH catalyst produced methyleugenolin 93.60% purity. Isomerization of methyleugenol employing base of potassium tertiary butoxide (t-BuOK) in dimethylsulfoxide (DMSO) gave methylisoeugenol with 87.15% yield and 98.10% purity. Oxidation of methylisoeugenol usingpotassium dichromate (K 2 Cr 2 O 7 ) was performed catalyst transfer phase (CTP) system of polysorbate 80 to 83.40% 3.4-dimethoxybenzaldehyde yield and 90.20% purity. Reduction of 3.4-dimethoxybenzaldehyde with sodium borohidrat (NaBH 4 )produced 98% yield. Halogenation of 3,4-dimethoxybenzyl alcohol by SOCl 2 to 3,4-dimethoxybenzyl chloride followed bynitrilisation using sodium cyanide produced 3.4-dimethoxybenzyl cyanide with 83.90% purity after reflux for 20 hours.